MON-LB57 Impact of Imputation Method and Response Cutoffs on Results From the Phase 3 OPTIMAL Study of Oral Octreotide Capsules in Adult Patients With Acromegaly - Samson, Susan Leanne (J Endocr Soc, 2020)
Objective: The phase 3 CHIASMA OPTIMAL study assessed efficacy and safety of oral octreotide capsules (OOC) in patients with acromegaly controlled on injectable somatostatin receptor ligands (SRLs). Sensitivity analyses were conducted for efficacy endpoints using two methods of imputation (i.e., the process of replacing clinical data with substitution values) to address missing data points due to some subjects reverting back to their prior injectable SRL treatment. Methods: Patients were ≥18 years of age and had evidence of active acromegaly with an average IGF-I ≤ 1.0 x ULN (utilizing the IDS iSYS assay calibrated to WHO recombinant reference standard 02/254). At baseline, patients were randomized to receive OOC or placebo for 36 weeks. The primary endpoint was proportion of patients maintaining biochemical response, defined as IGF-I ≤1.0 x ULN (2-value average at weeks 34 and 36) (Samson et al. ENDO 2020). Per study protocol, patient study discontinuations were considered non-responders regardless of clinical response at the time of discontinuation (non-response imputation). Additional exploratory analyses were performed utilizing the last observation carried forward (LOCF) analysis, as well as a completers analysis of response among the subgroup that completed the entire 36 weeks on study drug. The response rates reported for the primary end point are slightly adjusted for stratification differences as prespecified in the statistical analysis plan. Results: Twenty-eight patients received OOC and 12 failed to maintain biochemical response based on the primary endpoint. Seven of these 12 patients discontinued treatment early - 5 due to treatment failure and 2 due to AEs. The remaining 5 patients completed the 36-week protocol on study drug. Of these 5 patients, 4 had IGF-I values between >1.0 and ≤1.3 x ULN and 1 completed the study with an IGF-I of 1.7 x ULN with no clinical symptoms. 58.2% of patients in the OOC group met the primary endpoint of maintenance of biochemical response at the end of study using the non-response imputation. Using LOCF imputation, 64.3% (18/28) of patients met this endpoint. Of those completing the study (N=21), 76.2% maintained response. Conclusion: CHIASMA OPTIMAL primary endpoint was assessed using the non-response imputation for patients who discontinued treatment early, with a 58.2% response rate. However, when assessing the response rate based on LOCF imputation, or in study completers, similar to other phase 3 studies for acromegaly, the rate was imputed at 64.3% and 76.2%, respectively.